Two spectrophotometric methods for the determination of azithromycin and roxithromycin in pharmaceutical preparations - Ibrahim, Fawzia Ahmed; Wahba, Mary Elias Kamel; Galal, Galal Magdy (European Journal of Chemistry, 2017)
Two new and simple spectrophotometric procedures have been proposed and validated for estimation of two important macrolide antibiotics namely, azithromycin dihydrate and roxithromycin. Method I depends on complex formation between any of the two drugs and copper in acidic medium where the absorbances of the produced complexes are measured at 250 and 264 nm with linearity ranges of 1.0-100.0 and 2.0-130.0 µg/mL for the two drugs, respectively. Method II depends on the reaction of these drugs with N-bromosuccinimide forming a product which is yellow colored, measured at 264 and 278 nm, with linearity ranges of 2.0-140.0 and 3.0-160.0 µg/mL for azithromycin dihydrate and roxithromycin, respectively. The proposed methods were subjected to detailed validation procedure; moreover they were used for the estimation of the concerned drugs in their different dosage forms. Study of the reactions stoichiometry was carried out; furthermore, a reaction mechanism proposal was presented.